2015
DOI: 10.1073/pnas.1506093112
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila circadian rhythms in seminatural environments: Summer afternoon component is not an artifact and requires TrpA1 channels

Abstract: Under standard laboratory conditions of rectangular light/dark cycles and constant warm temperature, Drosophila melanogaster show bursts of morning (M) and evening (E) locomotor activity and a “siesta” in the middle of the day. These M and E components have been critical for developing the neuronal dual oscillator model in which clock gene expression in key cells generates the circadian phenotype. However, under natural European summer conditions of cycling temperature and light intensity, an additional promin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 34 publications
(29 reference statements)
4
78
1
Order By: Relevance
“…3a–c). These results were confirmed using a previously validated TrpA1 -RNAi32 transgene to knock down TrpA1 expression throughout the Drosophila nervous system using the pan-neuronal driver elav -GAL4. In the TrpA1 knockdown background, PMW was suppressed (Fig.…”
Section: Resultssupporting
confidence: 63%
“…3a–c). These results were confirmed using a previously validated TrpA1 -RNAi32 transgene to knock down TrpA1 expression throughout the Drosophila nervous system using the pan-neuronal driver elav -GAL4. In the TrpA1 knockdown background, PMW was suppressed (Fig.…”
Section: Resultssupporting
confidence: 63%
“…It has recently been shown that adult D. melanogaster display a mid-afternoon (A) peak of activity, but only when the afternoon temperatures reach above 30°C (Das et al, 2015;Green et al, 2015). This thermo-sensitive A peak was seen in simulated natural conditions in a controlled environment incubator where temperatures fluctuated from a low of 17 or 25°C to a peak of 32 or 35°C in the afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…When the variable light and temperature were out of phase, the A peak coincided with the highest temperature and not peak light levels (Das et al, 2015). Furthermore, the A peak requires a functioning neuronal temperature-sensitive transient receptor potential ion channel (TrpA1) (Das et al, 2015;Green et al, 2015). The afternoon peak of activity recorded for D. suzukii, including that of the mated females, occurred several hours after the hottest period and therefore is not equivalent to the temperature-sensitive A peak of D. melanogaster.…”
Section: Discussionmentioning
confidence: 99%
“…While these findings seem to be at odds with the results reported here (TRPA1 is required for a siesta during warm TCs rather than an increase in activity), it is clear that the experimental conditions are quite different. While we study the function of TRPA1 in light-independent conditions (total darkness), Green et al (2015) use changes of light and temperature. Moreover, it is difficult to compare the results between the studies, because the A peak is not observed in the temperature ranges where we identified a role for TRPA1 in repressing midday activity (20°C : 29°C).…”
Section: Discussionmentioning
confidence: 99%